The Influence of Herding Behavior on Cryptocurrency Investment Decision Among Investors in Bandung Raya Area - Zhafira, Aulia; Pramono, Tangguh Dwi (Universitas Kadiri, 2025)
This study explores how herding behavior influences cryptocurrency investment decisions among investors in Bandung Raya area. The study is driven by the growing involvement in digital asset markets and the psychological biases influencing investor actions. Using a quantitative method, data were collected from 157 purposively selected respondents through questionnaires and analyzed with IBM SPSS Statistics 27. The analysis included validity and reliability testing, descriptive statistics, classical assumption tests, correlation test and simple linear regression to assess the impact of herding behavior. The results reveal a significant and positive relationship between herding behavior and investment decisions, evidenced by a strong correlation coefficient of 0.863. Investors tend to follow the actions of others and market trends without conducting independent evaluations. This reflects a strong psychological inclination toward social conformity, particularly in high-volatility environments like the cryptocurrency market. The findings suggest that behavioral factors substantially shape investment choices, often outweighing rational decision-making. In conclusion, herding behavior emerges as a key factor in cryptocurrency investment decisions, highlighting the dominance of group influence. The study recommends enhancing financial literacy and behavioral finance education to foster better-informed investment practices.